The Development of Additional Materials in Kahoot! and the Use to Teach Reading Skill/ تطوير المواد الإضافية ببرنامج كاهوت واستخدامها لتعليم مهارة القراءة - Achmad Ivan Bahalwan; Putri Kurnia Wahidah (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2021)
The purpose of this research is to: (1) describe how to develop additional material using the Kahoot application and its use in learning reading proficiency for beginners, and (2) describe the level of effectiveness of additional material using the Kahoot application and its use in learning reading proficiency for beginners. This research uses Reiser and Mollenda's ADDIE development method, namely analysis, preparation, development, application, and evaluation. The results of this study are (1) Additional material using the Kahoot media consists of ten texts. The researcher developed 20 questions for each theme in multiple-choice form and based on three basic abilities, namely reading comprehension, vocabulary comprehension, and grammar comprehension. (2) The results of the field test show that this media is not yet effective for use in reading learning activities due to limitations in the application of the media due to the corona outbreak.